Formulasi dan Karakterisasi Nanopartikel Sambungsilang Gom Xantan dan Gom Akasia Untuk Penghantaran Insulin Oral - Rachmawati, Ade Laura; Surini, Silvia (Pharmaceutical Sciences and Research, 2018)
The insulin nanoparticles has been developed as an alternative to oral insulin delivery. Nanoparticle drug delivery system could be prepared by a cross-linked polymer, which was composed of xanthan gum and acacia gum, and cross-linked by sodium trimetaphosphate. The aim of the present study was to produce insulin nanoparticles using the cross-linked polymer of xanthan gum and acacia gum for oral delivery. In this study, insulin nanoparticles was prepared by mixing xanthan gum and acacia gum colloid with the ratio 1:1 and using sodium trimetaphosphate as a cross-linking agent in bases condition. Afterwards, insulin solution in HCl was added into the colloid, and then dried to produce the insulin nanoparticles. Insulin nanoparticle powders were characterized in terms of degree of substitution (DS), entrapment efficiency, Dv90, swelling ability, in vitro release study, and stability test. The results showed that the substitution degree of the insulin nanoparticles was 0.08 – 0.10 and the entrapment efficiency was 26.11% - 48.73%. Moreover, the insulin nanoparticles had Dv90 value 547 nm - 726 nm and swelling index of 1.1 - 2.9 in HCl pH 1.2 and 2.5 - 3.4 in phosphate buffer pH 6.8, respectively. According to the dissolution study, the insulin nanoparticles provided the insulin release of 78.42% - 85.67% within 3 hours. Furthermore, stability testing showed insulin content after 9 weeks incubation at 4oC was 74.46% - 85.09%. Therefore, this work demonstrated that a cross-linked polymer of xanthan gum and acasia gum nanoparticle could be potential for could be potential for oral insulin delivery system.